2016
DOI: 10.3390/lubricants4020012
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of the Lubricant Containing Titanium Dioxide Nanoparticles as an Additive

Abstract: Abstract:To improve the oil-solubility of nanoparticles, a new technology was used to prepare a kind of lubricant containing titanium dioxide (TiO 2 ) nanoparticles. The microstructures of the prepared nanoparticles were characterized via transmission electron microscope (TEM) and infrared spectroscopy (IR). Tribological properties of TiO 2 nanoparticles used as an additive in base oil were evaluated using four-ball tribometer and ball-on-disk tribometer. In addition, the worn surface of the steel ball was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…Their study has shown that the CuO nanoparticle has reduced the coefficient of friction compared to lubricants without nanoparticles. [26][27][28][29] They have also concluded that CuO nanoparticle has reduced this depth of wear scar compared with base lubricants. A study on the improvement of the anti-wear with customized palm oil with adding up of CuO and MoS2 was made and the results revealed that, the CuO and MoS2 nanoparticles were effective additives for incorporation into chemically modified palm oil and it has enhanced the anti-wear and extreme pressure properties by 1.5 times.…”
Section: Introductionmentioning
confidence: 98%
“…Their study has shown that the CuO nanoparticle has reduced the coefficient of friction compared to lubricants without nanoparticles. [26][27][28][29] They have also concluded that CuO nanoparticle has reduced this depth of wear scar compared with base lubricants. A study on the improvement of the anti-wear with customized palm oil with adding up of CuO and MoS2 was made and the results revealed that, the CuO and MoS2 nanoparticles were effective additives for incorporation into chemically modified palm oil and it has enhanced the anti-wear and extreme pressure properties by 1.5 times.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, nanofluid experiments conducted with conformal contact are also very limited. Most studies have been conducted using a ball or pin to slide against a disc rotationally . Therefore, the present research examines the tribological behaviour of oil‐based SnO 2 nanofluid using flat‐on‐flat reciprocating sliding tests.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research studies only focused on the tribological performance of nanofluids on hard metals such as cast iron and steel. 3,5,9,12 Little research was done to investigate antiwear and friction reduction characteristics of nanofluids on soft nonferrous materials such as aluminium and brass. In addition, nanofluid experiments conducted with conformal contact are also very limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on effect of TiO2 as an additive to oil are presented in [14,15]. The studies on the effect of TiO2 nanoparticles as an additive to liquid paraffin are presented in [16].…”
Section: Introductionmentioning
confidence: 99%